Maternal inflammation promotes fetal microglial activation and increased cholinergic expression in the fetal basal forebrain: role of interleukin-6 - Pratt, Lorelei; Ni, Li; Ponzio, Nicholas M.; Jonakait, G. Miller (Pediatric research, 2013)
Background: Perinatal exposure to infectious agents with associated maternal immune activation (MIA) leads to neuroanatomical and behavioral dysregulation reminiscent of autism spectrum disorders. Persistent microglial activation as well as increased choline acetyltransferase (ChAT) activity in the basal forebrain (BF) are characteristic of autistic subjects. Previous studies have shown that medium from activated microglia promotes cholinergic differentiation of precursors in the BF. We sought to determine whether MIA in vivo would lead to a similar effect on developing BF neurons. Methods: Pregnant mice were treated with the viral mimic polyinosinic–polycytidylic acid (poly(I:C)) or saline. Results: Poly(I:C) treatment resulted in increased production of cytokines and chemokines in fetal microglia and increased ChAT activity and cholinergic cell number in the perinatal BF. Whether microglial activation causes these changes is unclear. Examination of fetal brains from mice lacking interleukin-6 (IL-6 KOs) revealed an elevation in non–microglial-derived cytokines and chemokines over wild-type controls. Moreover, IL-6 KO offspring showed an elevation of ChAT activity even in the absence of poly(I:C) administration. Conclusion: These data suggest that elevations in cytokines and/or chemokines caused either by maternal poly(I:C) administration or by the absence of IL-6 are associated with alterations in cholinergic development in the BF.